If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 3(1 + -4b) = 38 + -4b 3 + (1 * 3 + -4b * 3) = 38 + -4b 3 + (3 + -12b) = 38 + -4b Combine like terms: 3 + 3 = 6 6 + -12b = 38 + -4b Solving 6 + -12b = 38 + -4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '4b' to each side of the equation. 6 + -12b + 4b = 38 + -4b + 4b Combine like terms: -12b + 4b = -8b 6 + -8b = 38 + -4b + 4b Combine like terms: -4b + 4b = 0 6 + -8b = 38 + 0 6 + -8b = 38 Add '-6' to each side of the equation. 6 + -6 + -8b = 38 + -6 Combine like terms: 6 + -6 = 0 0 + -8b = 38 + -6 -8b = 38 + -6 Combine like terms: 38 + -6 = 32 -8b = 32 Divide each side by '-8'. b = -4 Simplifying b = -4
| 4a+2b-3=9a-3b+3 | | 3p-1=5(p-1) | | 4=4a+2b-3 | | 6n+22-8n=42 | | A-4+9=21 | | b-2+2b=32 | | -114+10x=36+4x | | 2(3w-5)+4=15-(9x-4) | | -7(7+14x)-13x=-506 | | -110=-11b | | 2c-5=x+11 | | M-12-3=-96 | | X^5-6x-16x^3=0 | | 14x^2+28x+9=0 | | b^2+5b-2=0 | | -18-11x=5-10x | | -6=-m+5 | | 20-5(p+1)+3p=-(2p-15) | | 3w+6(u+1)-10=11w-3(4-2w) | | 3x+y+10=180 | | 6+0.10x=0-15x+8 | | .75(4x-8)=-8 | | M-12-3=-12 | | -8(10+5v)=-280 | | 10-6x=-20 | | 9x+15=14x | | -1.2x^2+2.9x+5=2.6 | | -7x-33=75-3x | | -26=10+4x | | S=0.8dh | | 9x^2+12x+9=0 | | 66-m-8=0 |